Ductility design of RC columns. Part 2: extent of critical zone and confinement reinforcement. Issue 1 (2nd January 2017) - Yuen, Terry Y P; Kuang, J S; Ho, Don Y B
ABSTRACT: The current Hong Kong concrete design code (HKConcrete2013), which is a non-seismic design code, includes provisions of the design of confinement zone in reinforced concrete (RC) columns. Whether or not these provisions can be adopted in the development of the new design code of structures for seismic resistance remains uncertain. A thorough scientific investigation with a comprehensive statistical analysis on the seismic behaviour of RC columns under different levels of the axial compression ratio (ACR) and concrete confinement has been conducted and presented in the companion paper [1 ], where the use of the ACR limits for controlling the seismic performance of various types of RC columns is proposed. The present paper addresses the important aspect of the confinement zone length and the design of confinement reinforcement in RC columns under different levels of the ACR. The theoretical background of the confinement zone is presented and the requirements of the prevailing design standards for designing confinement reinforcement in RC columns are critically compared and discussed. Design recommendations for the development of new provisions on the design of the confinement zone in RC columns are made for (1) the revision of the extent of the critical regions and (2) the introduction of the required quantity of the confinement reinforcement.